Analgesic efficacy of opioids in chronic pain: recent meta‐analyses. (1st July 2014) - Reinecke, H; Weber, C; Lange, K; Simon, M; Stein, C; Sorgatz, H
<x xml:space="preserve">Abstract</x> Opioids are regularly administered in acute and cancer pain. In chronic non‐cancer pain (CNCP), however, their use is controversial. Previous meta‐analyses and randomized controlled trials (RCTs) lack methodological homogeneity and comparable data. Here we analysed the maximum analgesic efficacies of opioids and non‐opioids compared with placebo, and of physiotherapy and psychotherapy compared with active or waiting‐list controls. We screened 3647 citations and included RCTs if treatment duration was at least 3 weeks, data were sufficient for meta‐analysis, and criteria for high quality were met. Only 46 studies (10 742 patients) met the criteria. Weighted and standardized mean differences (WMD, SMD) between pain intensities were pooled to conduct separate meta‐analyses for each treatment category. At the end of treatment the WMD for pain reduction (100‐point scale) was 12.0 for 'strong' opioids, 10.6 for 'weak' opioids, 8.4 for non‐opioids (each vs. placebo), 5.5 for psychotherapy and 4.5 for physiotherapy (each vs. active controls). Dropout rates were high in pharmacological studies. The 95% confidence intervals using the outcomes of control groups did not indicate statistical differences between efficacies of the five interventions. Because not enough eligible head‐to‐head trials were available, our analysis is limited to adjusted indirect comparisons. The heterogeneity of pre‐post pain differences in control groups did not allow the definition of a common comparator. In conclusion, although there were statistically significant differences between maximum treatment efficacies, no intervention per se produced clinically important improvements in average pain intensity. Thus, opioids alone are inappropriate and multimodal treatment programmes may be required for CNCP. Linked Articles This article is part of a themed section on Opioids: New Pathways to Functional Selectivity. To view the other articles in this section visit http://dx.doi.org/10.1111/bph.2015.172.issue-2